Bioactive profile and pharmacological activities of Eclipta Prostrata L. (Bangladesh Journal of Botany, 2026)
Eclipta prostrata L. has been used in traditional medicine due to its potential phytochemicals. In the current study, bioactive compounds such as tannins, terpenoids, flavonoids, and steroids were identified in the leaf extract. Moreover, the antibacterial assay showed moderate activity against bacteria. The HeLa cell line was treated with varying concentrations of methanolic leaf extract of E. prostrata which showed, approximately 95% of HeLa cells had died after 48 hours of incubation. The LD50 value for the methanolic extract was 75 mg/ml for HeLa cells. Eclipta prostrata extract exhibits significant cytotoxic effects on HeLa cells.Bangladesh J. Bot. 55(2): 347-353, 2026 (June)